A GALAXY SCHEMA APPROACH FOR INTEGRATING HETEROGENEOUS MACROECONOMIC DATA INTO AN ANALYTICAL DASHBOARD - Simanjuntak, Aurora Grace Valensia Pohan; Pinontoan, Benny; Soewoeh, Christian A. J. (POLITEKNIK SAINS DAN TEKNOLOGI WIRATAMA MALUKU UTARA, 2026)
Local economic data in Jayawijaya Regency, such as Gross Regional Domestic Product (GRDP), poverty rates, Human Development Index (HDI), and unemployment statistics, is often scattered across different spreadsheets and standard documents. This scattering considerably hinders deep, multi-aspect assessment for regional leaders. This study aims to build and deploy a dynamic analytical dashboard that aggregates economic figures for the period 2020-2024. The design of this system employs a Data Warehouse with a multidimensional Galaxy Schema to merge indicators with distinct measurement types into a single central place. The Extract, Transform, Load (ETL) process was automated using Pentaho Data Integration, achieving 100% data matching accuracy with no data loss. Using Tableau Public as the visual display section, the dashboard functions through three subject-based views: Executive Summary, Economic Growth, and Social Welfare.Keywords: Analytical Dashboard, Data Warehouse, Galaxy Schema, Macroeconomic, Visualization